Communication, heritage, and identity: The media’s discourse about the national party of cement in Olavarria, Argentina - Giacomasso, María Vanesa (2020)
The main objective of this work is to unveil the senses of identity built around the territory that comprises the Olavarria party (Buenos Aires province, Argentina), based on a historical analysis which recovers the discourse of the media as a fundamental agent in the socialization and consolidation of social imaginaries of the population. To accomplish this task, the graphic coverage of the Special Supplement of the newspaper Tribuna, which was published for the II National Cement Festival in Olavarria (1974), is analyzed. A methodology of discourse analysis was used to identify, in the journalistic narrative, the way in which meanings are represented and constructed in relation to identity and local cultural heritage. The main results of the analysis highlight the symbolic power of storytelling  in the media to build, reinforce and reproduce a mining identity brand linked to the cement industry in the Olavarria party, which has become a constituent aspect of the historical and cultural heritage of the city, and has been projected over time and remains alive today. This work is expected to contribute to the discussions about the leading role the graphic press has played in different historical moments and its influence on the local identity.